Firm Entry and Exit, Labor Demand, and Trade Reform : Evidence from Chile and Colombia - Fajnzylber, Pablo; Maloney, William F.; Ribeiro, Eduardo (World Bank, Washington, DC, 2014)
There are increasing fears that trade reform - and globalization generally - will increase the uncertainty the average (especially less skilled) worker faces. If product markets become more competitive and the access to foreign inputs is increased, will demand for workers among existing firms become more elastic? Will labor markets become more volatile because bad shocks to output will translate into greater impacts on wages and employment? So far the literature on this question has focused almost entirely on labor demand within continuing firms. But much of the movement in the job market arises from the entry and exit of firms. The authors show that firms entering and exiting a market contribute almost as much to employment changes as firms continuing in a market. In several samples, firms entering and exiting affected the net change in-positions more than the expansion of continuing plants did, although contributions varied greatly across the business cycle and period of adjustment. Estimates of labor demand elasticities of entering and exiting firms were surprisingly similar in Chile and Colombia and somewhat higher than elasticities for firms that survived. Estimates of the effect of trade liberalization offer only ambiguous lessons on trade reform's probable impact on these elasticities. The data suggest that in Chile greater exchange rate protection does reduce the wage-employment elasticity of entering and exiting plants, but the results are reversed in Colombia's case. Moreover, in Colombia higher import penetration lowers the elasticity of labor demand and in Chile higher tariffs increase it. These findings, combined with very ambiguous results from probit regressions on the determinants of plant exit, suggest that circumspection is warranted in asserting that trade liberalization will increase the wage elasticity of labor demand.